2006
DOI: 10.1097/01.mao.0000224080.77849.3d
|View full text |Cite
|
Sign up to set email alerts
|

Negative Effect of Immediate Hyperbaric Oxygen Therapy in Acute Acoustic Trauma

Abstract: Immediate HBOT in acoustic trauma treatment is not necessary; on the contrary, it has an adverse effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 15 publications
2
17
1
Order By: Relevance
“…Application of pre-or posttreatment via hyperbaric oxygen therapy (HBOT) has been widely reported to play a major protective role in the reduction of injured cochlear hair cells and a defensive role against acute NIHL (15)(16)(17)(18). However, several studies argue that HBOT may intensify the level of oxidative stress; the negative effect of HBOT on acute acoustic trauma has been also reported (19). Overall, there is no consensus regarding the ideal therapeutic time window or pressure for HBOT.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Application of pre-or posttreatment via hyperbaric oxygen therapy (HBOT) has been widely reported to play a major protective role in the reduction of injured cochlear hair cells and a defensive role against acute NIHL (15)(16)(17)(18). However, several studies argue that HBOT may intensify the level of oxidative stress; the negative effect of HBOT on acute acoustic trauma has been also reported (19). Overall, there is no consensus regarding the ideal therapeutic time window or pressure for HBOT.…”
Section: Discussionmentioning
confidence: 98%
“…Such negative effects may be associated with the increased level of cellular free radical species (such as ROS), caused by NBHO treatment within the first hour of noise exposure, which normally goes beyond the capacity of antioxidant defense mechanisms (19). In other words, time is needed for activation of indigenous defense enzymes to reduce the effects of ROS metabolites within the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Following a noise exposure, the hearing damage could also be due to the loss of the protective effect of the efferent fibres, perhaps mediated by the lateral olivocochlear neurons that synapse beneath the inner hair cells (Attanasio et al, 1999). The transitory auditory injury observed in our test group may also be related to the hyperbaric work environment: oxygen toxicity is a problem in diving and can have fatal consequences in the water; past experiences made on divers, highlighted the significant presence of hearing disturbances and disorientation, and demonstrated changes of the Central Nervous System in hyperbaric conditions (Cakir et al, 2006). Experiences done on animals (guinea pig) showed that repeated hyperbaric exposures that were considered to be safe did cause damage to the cochlear system (Zheng & Gong, 1992).…”
Section: Effects Of Sonar On Human Hearingmentioning
confidence: 89%
“…Acoustic trauma results in structural changes such as rupture of the cell membranes, reduction of cochlear b flow and destruction of cochlear hair cellsand/or dendrites of primary auditory neurons [1][2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…The hearing organ exposure to acoustic superstimulation by an intense impulse sound, may cause a sudden sensorineural hearing loss and occur due to altered cochlear oxygenation, decreased cochlear blood flow, damage to cell membranes, metabolic effects of free radicals, altered neurotransmission and apoptosis [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%